The Influence Of Budget Planning On Performance Regional Financial and Asset Agency (Empirical Study In Majalengka District) - Nurachman, Maman; Sopiah, Ida (Journal of Business, Accounting and Finance, 2024)
The government has performance demands that lead to the interests of society by realizing the government's vision and mission. In implementing the performance programe the government requires a budget in implementing work programs. Budget planning is a budget setting plan for a certain period to carry out a work program. This study aims to determine the effect of budget planning on the performance of financial institutions and regional assets in Majalengka Regency., Analysis of the Coefficient of Determination and Hypothesis Testing. Based on the data collected and testing the results, it shows that Budget Planning has a positive and significant effect on the Performance of Financial Institutions and Regional Assets in Majalengka Regency, as evidenced by the t_count value for Budget Planning is 4,720 and t_table with a = 5% is known to be 2,026, thus t_count is greater than t_table and a significance value of 0.000 <0.05. Based on the results of the determination test, budget planning has an influence on the performance of Financial Institutions and Regional Assets with an effect of 37% and the remaining 63% is influenced by other factors not included in this study. So it can be concluded that budget planning has a strong influence on the performance of the Financial Agency and Regional Assets of Majalengka Regency